YLLAPA USNO: RITUALS OF LIBATION, ANCESTORS CULT AND THE ANDES USHNU IDEA ACCORDING TO COLONIAL DOCUMENTS OF CENTURIES XVI-XVII - Pino Matos, José Luis (2010)
In the Andes, the rituals of libation were the most important social practice in the Inka ceremonies, which involved the entire social group starting with the most important as rulers, deities and the “Yllapa” or bodies of the deceased considered as principal. It is in this context that the “Ushnu” was the appropriate setting for such rituals with a leading role, and this was perceived and described subtly Spanish colonial records. The study based on an analysis of historical sources, shows the detailed description of these places and the complexity and multifunctionality of the “Ushnu,” in relation to the rituals of libation and ancestor worship by the Andean societies. It also raises the possibility of using a large number of the “Yllapa Usno” or receptacles for libations that might have a movable character, and every ancestor of every social group had to give theirs.